2022
DOI: 10.1038/s41598-022-21787-z
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the COVID-19 fatality rate and altitude association through a comprehensive analysis

Abstract: The emergence of COVID-19 virus has led to a pandemic with staggering morbidity and mortality. There is evidence showing that pre-existing conditions and environmental factors are associated with worse COVID-19 outcomes. Among these conditions, altitude is of particular interest. Altitude has been shown to influence the morbidity and mortality of multiple chronic pathologies such as cardiovascular disease, chronic obstructive pulmonary disease and lung cancer. COVID-19 fatality rate has been associated with as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Due to Bogotá’s location at 2,640 m above sea level, PaO 2 is around 60 mmHg and SaO 2 is 90% in normal patients, with significant desaturations during exercise in patients with interstitial lung disease ( 11 ). Despite these lower saturations at altitude, different studies suggest that this does not represent a negative impact on the mortality of patients with COVID-19 residing at high altitudes ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to Bogotá’s location at 2,640 m above sea level, PaO 2 is around 60 mmHg and SaO 2 is 90% in normal patients, with significant desaturations during exercise in patients with interstitial lung disease ( 11 ). Despite these lower saturations at altitude, different studies suggest that this does not represent a negative impact on the mortality of patients with COVID-19 residing at high altitudes ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological adaptations and genetic characteristics of individuals who live at high altitudes have been described as factors associated with lower mortality, higher probability of hospital discharge, and higher survival [ 34 , 39 , 40 , 41 , 42 , 43 ]. Notably, the most widely described factors that could account for the lower mortality rates in high-altitude populations are as follows: the hypobaric hypoxia in response to long-term exposure to high altitude and the resulting improved lung capacity, the reduced expression of the angiotensin-converting enzyme, and the higher levels of inflammatory cytokines (such as IL-6 y TNFα), hemoglobin, and erythropoietin [ 39 , 40 , 44 , 45 ]. It has also been reported that, compared to individuals residing in low-altitude areas, COVID-19 cases residing in high-altitude areas may present with low levels of fibrinogen and platelets, and disturbed electrolyte levels [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent reports have shown that COVID-19 infection rates are lower at higher altitudes 5,[7][8][9][10][11][12][13][14][15] . As it concerns mortality, findings remain unclear [16][17][18][19] but again have been attributed to the low population density at high-altitude 20 . Thus, a comprehensive analysis of the relationship between COVID-19 mortality and altitude was conducted for the highlands of the United States.…”
Section: Introductionmentioning
confidence: 99%